K * Loops and the Strangeness Radius and Magnetic Moment of the Nucleon - Barz,L.L. (1997)
In this work we extend previous kaon loop calculations, including the vector K* meson and estimate the strangeness radius of the nucleon and its strange magnetic moment. We find out that, in contrast to naive expectations, this contribution is very important and gives large values for both the radius and the magnetic moment